(untitled) (Research, Society and Development, 2022)
Produced by the bacterium Clostridium botulinum, the application of botulinum toxin in dental procedures is increasing and targeted by patients, this because it presents effective protocols and safe techniques. Therefore, the present study aimed to carry out a literature review about the application of botulinum toxin as a therapeutic measure for bruxism and gummy smile. To this end, searches were carried out on PubMed, Scientific Electronic Library Online and Virtual Health Library platforms using the descriptors: “Botulinum Toxins, Type A”, “Dental Care” and “Esthetics”. Bruxism is an oral disorder that may involve multiprofessional treatment and is characterized by clenching or grinding the teeth, pushing or not the jaw, which occurs during the day or night, affecting the stomatognathic system. The literature has shown that botulinum toxin is an excellent alternative in the treatment not only for aesthetics, but also in cases of bruxism and gummy smile. It is a gingival smile when, in the act of smiling, there is exposure of the gingiva greater than three millimeters, with a higher prevalence in women. The effect of the drug is individualized, varying according to the patient, however it is guaranteed to be safe and with a high rate of clinical success. Therefore, the professional must have knowledge about facial anatomy and substance application techniques.